Anonymous access protocol for media independent information service - LI Guang-song1; MA Jian-feng1; JIANG Qi1 (Tongxin xuebao)
For anonymous access requirements of media independent information service（MIIS） in heterogeneous networks,an access protocol with user anonymity was proposed.With the aid of the home server,the mobile user and the information server mutually authenticated each other while keeping the mobile user anonymous.Compared with other schemes,the proposed protocol has better performance,and it is provably secure in the CK model.